THE SIGNIFICANCE AND PROSPECTS OF THE CONSTITUTIONAL REFORMS IMPLEMENTED IN UZBEKISTAN - X. Muhammedov (Modern American Journals, 2025)
This article analyzes the constitutional reforms implemented in Uzbekistan since 1992, their role in the development of public administration, civil society, and the rule of law. It also highlights the main directions of the reforms and their future prospects. The author reveals the contribution of constitutional changes to ensuring the rights and freedoms of citizens.
Keywords: Constitutional reforms, rule of law, civil society, human rights, democracy, Constitution of Uzbekistan.